Effect of 29 weeks of periodized soccer training on the neuromuscular performance of soccer players under 20 years of age - Corrêa, D. A.; Soares, D. S.; Gonelli, P. R. G.; Cesar, M. C.; Sindorf, M. A. G.; Crisp, A. H.; Verlengia, R.; Balbino, H. F.; Lopes, C. R. (Journal of Exercise Physiology online, 2016)
The purpose of this study was to investigate the effects of 29 weeks of periodized soccer training (linear during pre-season and ondulatory during the competitive period) on the neuromuscular performance of soccer players under 20 yrs of age. Ten regionally ranked male athletes (19.2 ± 1.3 yrs, body mass 71.1 ± 6.8 kg, height 179.0 ± 0.2 cm) participated in this study. The pre-season physical training program lasted 9 wks. The competitive period lasted 19 wks. The assessments were conducted at specific times during training periodization: baseline, 4, 8, and 19 wks. The results showed improvements in squat jump performance and maximal strength during the pre-season and the competitive period, respectively. On the other hand, repeated sprint ability and the 15-m sprint performance were reduced at the end of competitive period. Thus, the findings indicate that 29 wks of periodized soccer training increased the soccer players` maximum strength and maintained their vertical jump performance. However, the models adopted did not improve repeated sprint ability and the 15-m sprint time.